Prevalence of posttraumatic stress disorder and associated disorders among adolescents in public schools: a crosssectional study - ASTITENE, KHALID; BARKAT, AMINA (International Journal of Psychosocial Rehabilitation, 2024)
Anyone can develop post-traumatic stress disorder (PTSD) following a traumatic event; thisdisorder can develop comorbid PTSD disorders such as anxiety and depression which couldseriously interfere with the daily life of the adolescent who was be the subject of our study byevaluating the prevalence of PTSD in public schools and also evaluating the impact of thisdisorder. Among 94 schools, 10 high schools and 15 middle schools were selected. 1250students were selected for a cross-sectional survey with an age of 12 to 17 years (14.98 ±1.49). The survey was carried out during the period from March to June 2017. Standardizedquestionnaires (Life Events Checklist, CPTS-RI, STAIY and CDI) were used. A highprevalence of PTSD was found with 44.4% which is explained by the inclusion of the date ofevent from 1 month to 3 months and the specificity of a population of Moroccanschoolchildren (lack of social support, parental illiteracy, poverty, precariousness,unemployment) with 62% of PTSD in girls versus 38% in boys (p